Pemikiran Gusdur dalam Buku Islam Kosmopolitan dan Pendidikan Demokrasi - Humaedi (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2017)
Democratic civic education for Indonesian people has been carried out in various forms. During Soekarno's old order, democratic education was published on the concept of "Unity in Diversity", one National language (Indonesian), a spirit of anti-imperialism and loyalty to the country. During Suharto's New Order administration, democratic education was manifested through the P-4 upgrading program (Guidelines for the Understanding and Practicing of the Pancasila) which served as a tool to describe the "archipelago insight" or perspective of the Indonesian people. Gus Dur said; democracy must take and give. No one can force others to give up their religious beliefs. Democracy is providing a set of core democratic values ​​or democratic attitudes such as respecting reasonable differences. Democracy education is understood as the process of individual awareness of human rights. Therefore Muslims must be able to emphasize that Islam supports and respects human rights.